1999
DOI: 10.1128/jvi.73.5.4009-4018.1999
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Macaques against Pathogenic Simian/Human Immunodeficiency Virus 89.6PD by Passive Transfer of Neutralizing Antibodies

Abstract: The role of antibody in protection against human immunodeficiency virus (HIV-1) has been difficult to study in animal models because most primary HIV-1 strains do not infect nonhuman primates. Using a chimeric simian/human immunodeficiency virus (SHIV) based on the envelope of a primary isolate (HIV-89.6), we performed passive-transfer experiments in rhesus macaques to study the role of anti-envelope antibodies in protection. Based on prior in vitro data showing neutralization synergy by antibody combinations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
176
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 724 publications
(179 citation statements)
references
References 54 publications
(57 reference statements)
3
176
0
Order By: Relevance
“…Similar findings with regard to the relationship between neutralization and protection are apparent for challenge of macaques with chimeric SIV/HIV (SHIV) viruses (Baba et al, 2000;Mascola et al, 2000;Shibata et al, 1999). In one instance of mucosal challenge, partial protection was described for a serum mAb concentration corresponding to only about 90% neutralization in vitro (Mascola et al, 1999). Recently, however, we have found that protection from mucosal challenge with an R5 SHIV virus required mAb concentrations capable of neutralizing essentially all of the challenge virus (Parren et al, 2001b).…”
Section: B Retrovirusessupporting
confidence: 55%
“…Similar findings with regard to the relationship between neutralization and protection are apparent for challenge of macaques with chimeric SIV/HIV (SHIV) viruses (Baba et al, 2000;Mascola et al, 2000;Shibata et al, 1999). In one instance of mucosal challenge, partial protection was described for a serum mAb concentration corresponding to only about 90% neutralization in vitro (Mascola et al, 1999). Recently, however, we have found that protection from mucosal challenge with an R5 SHIV virus required mAb concentrations capable of neutralizing essentially all of the challenge virus (Parren et al, 2001b).…”
Section: B Retrovirusessupporting
confidence: 55%
“…During natural infection, they appear to have little impact on acute viremia, as they arise too late and the virus readily escapes type-specific neutralizing antibodies (35,41,42,55). However, passive transfer of broadly neutralizing monoclonal antibodies (MAbs) has proven to be protective in nonhuman primate models (2,11,17,18,27,28,52), supporting the hypothesis that a vaccine capable of inducing this type of antibodies is likely to be effective. Despite rigorous efforts, designing an immunogen capable of inducing broadly neutralizing antibodies has so far not been feasible.…”
mentioning
confidence: 99%
“…However the four well-known HIV-1 neutralising antibodies, namely, 2G12, 4E10, 2F5 and b12 have been well researched in terms of structure, interaction with the virus, protection in animal models and safety in clinical trials and were produced in various plant platforms. These antibodies have fared well in protecting macaques from systemic or vaginal Simian/Human immunodeficiency virus (SHIV) challenges and are well tolerated in human subjects (Armbruster et al, 2002(Armbruster et al, , 2004Hessell et al, 2010;Mascola et al, 1999Mascola et al, , 2000Parren et al, 2001). Furthermore, passive administration of neutralising monoclonal antibodies (MAbs) 4E10, 2F5 and 2G12 reduced viral rebound in established HIV infections (Trkola et al, 2005).…”
Section: Production Of Hiv Neutralising Antibodies In Plantsmentioning
confidence: 99%
“…It docks onto to the core epitope ELDKWA on the lipid embedded membrane proximal exterior region (MPER) of gp41 and potentially interferes with the fusion step of the virus (Binley et al, 2004;de Rosny et al, 2004;Franquelim et al, 2011;Muster et al, 1993). On its own and in combination with other antibodies including 2G12 and 4E10, 2F5 displayed the ability to protect against an intravenous, vaginal and oral challenge of SHIV in macaques (Baba et al, 2000;Hessell et al, 2010;Mascola et al, 1999Mascola et al, , 2000. Furthermore passive administration of this antibody did not seem to cause immune responses or other adverse effects in HIV infected human participants (Armbruster et al, 2004).…”
Section: F5mentioning
confidence: 99%